Descriptions of five new species of the Neotropical Mictopsichia group of genera (Lepidoptera: Tortricidae) - Razowski, Józef (Zootaxa, 2011)
Five new species of the Mictopsichia group of genera are described and illustrated: Mictopsichia misahuallia (type locality: Napo Province, Ecuador), Mictopsichia chirripoana (type locality: San José Province, Costa Rica), Rubropsichia kartaboana (type locality: Bartica District, British Guiana), Chamaepsichia cetonia (type locality: Heredia Province, Costa Rica), and Chamaepsichia chitonregis (type locality: T. F. Amazonas, Venezuela). Although the systematic placement of the group is enigmatic, continued assignment to Archipini is recommended.